KRITERIA MEMILIH PASANGAN MENIKAH BAGI GEN Z BERDASAR STANDARISASI TIK TOK PERSPEKTIF MASLAHAH MURSALAH - Deswinta, Deswinta; Silvia Putri, Rizky; Yasir Fauzi, Mohammad (IAIN BONE, 2025)
The development of digital technology has reconstructed the pattern of social interactions among the younger generation, particularly Gen Z, who are increasingly influenced by identity representation through social media platforms such as TikTok. This platform no longer functions merely as a means of entertainment but has evolved into a space for identity production and social standardization, including in defining criteria for life partners. This study aims to examine how partner standards formed on TikTok are understood and negotiated by students of the 2022 cohort of the Islamic Family Law Study Program at UIN Raden Intan Lampung, from the perspective of Maslahah mursalah. Using a descriptive-analytical qualitative approach through questionnaires distributed to 91 respondents, the study finds that although TikTok provides an initial influence in constructing perceptions of the ideal partner, final decisions are filtered through religious values, morality, and the principles of maqasid al-shariah. TikTok serves only as a secondary reference, while religiosity, morality, and responsibility are positioned as primary criteria. The findings affirm that young Muslim generations possess digital literacy capacities grounded in Islamic values and are able to negotiate algorithmic standards with Sharia-based norms.